2014
DOI: 10.1177/1470320314539827
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin-converting enzyme gene insertion/deletion polymorphism and pancreatitis risk: A meta-analysis

Abstract: Objective: Many studies have focused on the relationship between the angiotensin-converting enzyme gene (ACE) insertion/deletion (I/D) polymorphism and pancreatitis risk, but the results remain inconsistent. Thus, a meta-analysis was carried out to derive a more precise estimation of the association between ACE I/D polymorphism and pancreatitis risk. Methods: Relevant publications were searched in several widely used databases and seven studies from six eligible articles were included in the meta-analysis. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…A variant in the ACE gene was previously reported as having a positive association with AP, but this was not confirmed in the present study; meta-analysis of the ACE insertion-deletion (rs4646994) in 245 patients and 1455 controls showed a positive association with the insertion 23 . This meta-analysis was updated with a large study, and the association was lost in both genetic models.…”
Section: Discussioncontrasting
confidence: 99%
“…A variant in the ACE gene was previously reported as having a positive association with AP, but this was not confirmed in the present study; meta-analysis of the ACE insertion-deletion (rs4646994) in 245 patients and 1455 controls showed a positive association with the insertion 23 . This meta-analysis was updated with a large study, and the association was lost in both genetic models.…”
Section: Discussioncontrasting
confidence: 99%
“…They discovered that the rs5275 polymorphism in the 3′-untranslated section of the COX-2 gene was allied with vulnerability towards AP (Fang et al, 2015;James et al, 2015).…”
Section: Ptgs2mentioning
confidence: 99%
“…Therefore, the specific RAS in the pancreas directly correlates with AP, as the RAS activates the inflammatory signaling pathway by activating the immune cells to release proinflammatory cytokines, which is one of the causes leading to AP. Fang et al carried a meta-analysis study on the polymorphism involved with the ACE gene in association with the risk of AP, and the study consists of 3 countries with 544 patients and reported that this polymorphism is directly associated with alcohol-related AP (Fang et al, 2015). The authors have also reported that there will be impairment in the mitochondria causing chronic hypoxia on continuous alcohol intake and thus leading to AP.…”
Section: Genes Regulating For Angiotensin-converting Enzymementioning
confidence: 99%
“…RAS can also activate immune cells to release proinflammatory cytokines, leading to the activation of the inflammatory signaling pathway. A meta-analysis combining several studies revealed an insertion/deletion (I/D) polymorphism of the ACE gene that increases the risk for AP [ 41 ]. Furthermore, a study that combined 544 patients from 3 countries showed that this polymorphism is associated with alcohol-related AP ( P = 0.03) [ 42 ].…”
Section: Early-stage Ap: Two Early Events In Acinar Cellsmentioning
confidence: 99%